High‐Performance Multilayer Encapsulation for Perovskite Photovoltaics. Issue 24 (1st July 2018) - Wong‐Stringer, Michael; Game, Onkar S.; Smith, Joel A.; Routledge, Thomas J.; Alqurashy, Bakhet A.; Freestone, Benjamin G.; Parnell, Andrew J.; Vaenas, Naoum; Kumar, Vikas; Alawad, Majed O. A.; Iraqi, Ahmed; Rodenburg, Cornelia; et al.
Abstract: An encapsulation system comprising of a UV‐curable epoxy, a solution processed polymer interlayer, and a glass cover‐slip, is used to increase the stability of methylammonium lead triiodide (CH3 NH3 PbI3 ) perovskite planar inverted architecture photovoltaic (PV) devices. It is found this encapsulation system acts as an efficient barrier to extrinsic degradation processes (ingress of moisture and oxygen), and that the polymer acts as a barrier that protects the PV device from the epoxy before it is fully cured. This results in devices that maintain 80% of their initial power conversion efficiency after 1000 h of AM1.5 irradiation. Such devices are used as a benchmark and are compared with devices having initially enhanced efficiency as a result of a solvent annealing process. It is found that such solvent‐annealed devices undergo enhanced burn‐in and have a reduced long‐term efficiency, a result demonstrating that initially enhanced device efficiency does not necessarily result in long‐term stability. Abstract : An encapsulation system is developed comprising of a UV‐curable epoxy, a polymer interlayer and a glass coverslip. Encapsulation is used to protect perovskite PV devices that are exposed to AM1.5 irradiation for 1000 h. Devices maintain 80% of their initial power, however a solvent‐anneal process used to increase device efficiency results in reduces long‐term stability.